Noble gases in micrometeorites from the Transantarctic Mountains - Baecker, Bastian; Ott, Uli; Trieloff, Mario (Geochimica et cosmochimica acta, 2018)
The bulk of extraterrestrial matter currently accreted by the Earth is in the form of micrometeorites (MMs) and interplanetary dust particles (IDPs), thus they may have collectively made a substantial contribution to the volatile inventory of the Earth and the other terrestrial planets. We have performed a complete noble gas study, accompanied by a complete petrographic characterization, of MMs from the Transantarctic Mountain (TAM) collection in the size range ∼300 to ∼1000µm that fell over an extended time period during the last ∼1Ma. Our noble gas study includes krypton and xenon, which have been largely missing in previous work. Helium and neon are dominated by a solar component, with generally lower abundance in scoriaceous MMs than in unmelted ones, and also generally lower in abundance than in previously studied MMs, which may be explained by the larger particle size (surface/volume ratio) of the MMs we studied. Considering an enhanced MM flux in the early Solar System, such MMs may have supplied a significant fraction of Earth’s neon. A number of MMs have kept what was probably their pre-terrestrial He/Ne ratio, from which we infer that the observed solar component is retained in a tiny surface region not affected by atmospheric entry. The abundances of (volume-correlated) heavier gases are similar to what was found in previous studies of smaller MMs. While Ar contains both solar and “planetary” contributions, the heavy noble gases (Kr, Xe) generally show “planetary” patterns but are often also compromised by terrestrial contamination as evidenced by an enhanced Kr/Xe ratio. Kr and Xe in a subset of scoriaceous MMs are dominated by isotopically fractionated air, possibly acquired during the passage through Earth’s ionosphere. Those not obviously affected by air show isotopic ratios similar to primitive meteorites (the Q component), thus primordial heavy gases supplied to the Earth by MMs are likely as those found in macroscopic meteorites. There is no evidence for the presence of a “cometary” Xe component as identified in the coma of comet 67P/Churyumov-Gerasimenko, hence a cometary source for a significant fraction of MMs in the studied size range is unlikely. Cosmogenic helium, neon and argon were detected in several cases. Cosmic ray exposure ages were calculated based on cosmogenic 21Ne in combination with the Poynting-Robertson effect, but depend on assumptions about atmospheric entry loss. Still, several cases are consistent with an origin from the asteroid belt (even assuming no loss) and one scoriaceous MM (#45b.17) would have to originate from beyond Jupiter. In at least two cases, including #45b.17, the isotopic composition of cosmogenic Ne appears to be inconsistent with predominant production in small particles free-floating in space, however; much of the irradiation of these MMs may have occurred when they were part of larger parent bodies.